2018
DOI: 10.1111/ajag.12553
|View full text |Cite
|
Sign up to set email alerts
|

Experiences of older people following the introduction of consumer‐directed care to home care packages: A qualitative descriptive study

Abstract: Many aspects of the initial implementation of CDC were challenging for older people. Clear, relevant and timely communication and information about CDC and its consequences for consumers appear to be needed to enhance CDC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(35 citation statements)
references
References 17 publications
2
18
1
Order By: Relevance
“…Interestingly, the negative attitudes of consumers towards CDC found in some other studies (Day et al., 2018; Gill et al., 2018; KPMG, 2015) were not found in this study. This difference may have resulted because CDC was being imposed in the previous studies, whereas participation in this trial was voluntary.…”
Section: Discussioncontrasting
confidence: 75%
See 2 more Smart Citations
“…Interestingly, the negative attitudes of consumers towards CDC found in some other studies (Day et al., 2018; Gill et al., 2018; KPMG, 2015) were not found in this study. This difference may have resulted because CDC was being imposed in the previous studies, whereas participation in this trial was voluntary.…”
Section: Discussioncontrasting
confidence: 75%
“…Studies of these trials and the early implementation of CDC found little change from traditional service provision. Participants were unaware of choices in service delivery and costs and they gratefully accepted whatever services were offered (Day et al., 2018; Gill, Bradley, Cameron, & Ratcliffe, 2018; Gill & Cameron, 2015). Inflexible service design and negative staff attitudes inhibited change (Day et al., 2018; Gill & Cameron, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results are consistent with previous research. 6,7,13 Also impacting on people's ability to make optimal use of their package funds is an immature market, with gaps in desired services on the supply side as well as consumers lacking both information and confidence on the demand side. Consistent with this is recent research which indicates that people who have held packages for longer have an improved ability to manage package funds effectively.…”
Section: Discussionmentioning
confidence: 99%
“…6 Communication about packages, and budgets in particular, was reported as insufficient to support effective decision-making. 7 The Australian Government's MyAgedCare website is designed to be a key source of information about government-funded aged care service. 8 It provides information about available services (including costs), and assessment and referral processes to access services.…”
Section: Introductionmentioning
confidence: 99%